Assessment of the GenoType MTBDRsl VER 2.0 compared to the phenotypic drug susceptibility testing and whole genome sequencing for the rapid detection of resistance to fluoroquinolone and second-line injectable drugs among rifampicin-resistant Mycobacterium tuberculosis isolates - Kardan-Yamchi, Jalil; Amini, Sirus; Hamzelou, Gholamreza; Rahimi Foroushani, Abbas; Ghodousi, Arash; Cirillo, Daniela Maria; Feizabadi, Mohammad Mehdi (Archives of microbiology, 2021)
Molecular techniques have considerable advantages for rapid detection, a reduction of infectiousness, prevention of further resistance development and surveillance of drug-resistant TB. MTBDR sl VER 2.0 was used to detect resistance to second-line anti-tuberculosis drugs on 35 rifampicin-resistant M. tuberculosis (RR-MTB) isolates compared to the minimum inhibitory concentrations (MICs) and whole genome sequencing (WGS). The MTBDR sl VER 2.0 (Hain Life Science, Nehren, Germany) and WGS (San Diego, CA, USA) were performed for tracing mutations in resistant-related genes involved in resistance to fluoroquinolone (FLQ) and second-line injectable drugs. The broth microdilution method using 7H9 Middlebrook media supplemented with OADC was used to determine the MICs. The MTBDR sl VER 2.0 correctly detected 5/6 (83.3%) of FLQ-resistant strains. The MUT1 A1401G (seven strains) and MUT2 G1484T (one strain) mutations in rrs gene were detected in eight AMK/KAN/CAP-resistant strains. Four low-level KAN-resistant strains with the G-10A/C-12T (three strains) and eis C-14T (one strain) mutations in eis gene was diagnosed using MTBDR sl VER 2.0. Five errors were found in detecting resistance to kanamycin and capreomycin compared to the phenotypic drug susceptibility testing and WGS. Failling wild-type bands without improved mutant bands did not indicate a reliable resistance. WGS could efficiently resolve the discrepancies of the results. MTBDR sl showed better performance in detecting XDR strains than pre-XDR.